Sustainable Development, Green Chemistry, and Its Applications - Aleza Rizvi; Omveer Singh; Syed Shariq Mian; Desh Deepak Pandey; Rinkesh Kumar; Rizwan Ul Hasan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Green chemistry (GC)–the design of chemical processes that reduce or eliminate hazardous substances – provides a framework for achieving sustainable development in industry and technology. This review summarizes recent advances (2020–2024) and emerging trends in green chemistry, highlighting how new catalysts, solvents, and biotechnologies are enabling cleaner processes. Key topics include alternative solvents (water, supercritical CO₂, ionic liquids, deep eutectic solvents), novel catalysts (metal, photocatalytic, and biocatalytic systems), and renewable feedstocks (biomass, CO₂). We discuss case studies such as plant-based PET (“Plant Bottle”) and biodegradable polymers, and note how industry adoption of GC principles has already reduced waste and emissions. We also examine current challenges – economic, regulatory, and technical barriers that slow implementation – and outline future directions (AI-driven process design, electrification of synthesis, circular economy). The content is presented for an audience of chemistry and environmental science students, with references to recent literature.